Construction of direct Z-scheme photocatalyst by the interfacial interaction of WO3 and SiC to enhance the redox activity of electrons and holes. (November 2021) - Li, Ping; Guo, Jiangna; Ji, Xing; Xiong, Yuli; Lai, Qingxin; Yao, Shuangrui; Zhu, Yan; Zhang, Yunhuai; Xiao, Peng
Abstract: The direct Z-scheme heterojunction structure benefits separation and migration of photoinduced carriers while maintaining original redox ability of each component. Nowadays, most Z-scheme structures are fabricated by g-C3 N4 with other narrow band photocatalysts due to its low conduction band (CB). In this paper, SiC, another kind of photoelectric semiconductor with low CB, was employed to prepare direct Z-scheme photocatalyst with 2D WO3 by simple water oxidation precipitation method. The component and interface band structure of Z-scheme heterojunction WO3 /SiC (WS) were verified by XPS, KPFM, Mott-Schottky method. The photodegradation efficiency and rate constant values of WS-1 for degrading RhB enhanced 2.5 and 5.3 times respectively compared with pristine WO3 . Radical capture experiments and ESR tests affirmed that WS-1 photocatalyst produced OH and O2 － active species, which further confirmed the photogenerated carriers were transmitted through the Z-scheme mode in principle. Band structure investigation showed that the direct Z-scheme structure assembled by WO3 with high valence band (VB) and SiC with low CB could maintain the high photocatalytic activity of active species. Therefore, this study offers a feasible method for construction of a novel and efficient direct Z-scheme photocatalyst. Highlights: Novelty direct Z-scheme WO3 /SiC heterojunction is firstly synthesized. The interface band structure of WO3 /SiC heterojunction is verified. High VB potential of WO3 and low CB potential of SiC are utilized simultaneously. Photodegradation efficiency of WO3 /SiC is 2.5 and 42.1 times than that of WO3 and SiC.